2017
DOI: 10.4103/sajc.sajc_160_16
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of two different modalities in the management of choroidal melanoma in the Asian Indian population

Abstract: Background:Choroidal malignant melanoma is a rare intraocular cancer in Asian Indian population. There is a paucity of data from our population comparing iodine 125 (I-125) brachytherapy and enucleation.Aim:This study aims to compare two groups of choroidal melanoma patients treated with either I-125 brachytherapy or enucleation in the Asian Indian population.Objectives:To evaluate the long-term morbidity and mortality rates in choroidal melanoma patients treated with either I-125 brachytherapy or enucleation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 1 It is more prevalent in the Caucasian population with an incidence of about 5.1 cases per million populations per year in the USA. 2 Earlier reports have showed that the survival rates decrease with an increase in tumor thickness in every millimeter; for example, the 10-year survival rate declined from 92% for thickness ≤1 mm to 50% with melanoma thickness >4 mm. 3 The two main pathogenic factors for melanoma are genetic predisposition and environmental factors.…”
Section: Introductionmentioning
confidence: 97%
“… 1 It is more prevalent in the Caucasian population with an incidence of about 5.1 cases per million populations per year in the USA. 2 Earlier reports have showed that the survival rates decrease with an increase in tumor thickness in every millimeter; for example, the 10-year survival rate declined from 92% for thickness ≤1 mm to 50% with melanoma thickness >4 mm. 3 The two main pathogenic factors for melanoma are genetic predisposition and environmental factors.…”
Section: Introductionmentioning
confidence: 97%
“…Advantages of 106 Ru are its relative ease of availability, long shelf-life, ease of reuse, and its sparing effect on surrounding healthy tissues. A study conducted among Asian Indians comparing enucleation versus brachytherapy yielded similar survival rates in both groups and intergroup observations were not statistically significant [27]. Local resection of tumor has been described in the literature.…”
Section: Treatmentmentioning
confidence: 91%
“…Modified Callendar Classification is widely used histopathological classification of UM worldwide [26]. Studies from India [15,27] and China [11] showed a higher incidence of spindle type tumor as compared to mixed celltype tumor. Table 3 summarizes the histopathological features and treatment modalities in various Asian studies.…”
Section: Based On Histopathologymentioning
confidence: 99%
“…The annual incidence of UM in Asia is 0.25 cases per one million individuals, but the age-standardized incidence rate increased recently to 0.60 cases per one million individuals [ 3 , 4 ]. Because of the limited number of cases, there have been a few studies reporting treatment outcomes, toxicity, or prognoses of UM in Asia [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%